Allegations in the New Peruvian Labor Proccess Law - Vinatea Recoba, Luis (2014)
The New Labor Procedure Act has generated many changes in the structure of the labor process itself: It has turned from being written and unfocused to become now an oral and concentrated one. As a consequence, there's only once chance for convincing the Judge.This article covers the strategy to be followed in this new process, from the strategy itself to the allegations, in order to generate certainty in the judge whom will solve the case.